NGTS clusters survey – II. White-light flares from the youngest stars in Orion. Issue 1 (7th July 2020) - Jackman, James A G; Wheatley, Peter J; Acton, Jack S; Anderson, David R; Belardi, Claudia; Burleigh, Matthew R; Casewell, Sarah L; Eigmüller, Philipp; Gill, Samuel; Gillen, Edward; Goad, Michael R; Grange, Andrew; et al.
ABSTRACT: We present the detection of high-energy white-light flares from pre-main-sequence stars associated with the Orion Complex, observed as part of the Next Generation Transit Survey (NGTS). With energies up to 5.2 × 10 35 erg these flares are some of the most energetic white-light flare events seen to date. We have used the NGTS observations of flaring and non-flaring stars to measure the average flare occurrence rate for 4 Myr M0–M3 stars. We have also combined our results with those from previous studies to predict average rates for flares above 1 × 10 35 erg for early M stars in nearby young associations.